Study the mineralogy of Al-Faw soil in southern Iraq and determine swelling properties by indirect methods - Haneen.N. Abdalamer - Huda.A.Daham ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
This study aims to determine the capacity of surface soils, the loading layers of engineered structures with shallow foundations, to swell. For this, five samples were collected using a hand auger at a depth of 1.5–2 meters in the city of Al-Faw in Basra, Iraq. The swelling potential of the soils in the research area was calculated using the clay content, liquid limit, plasticity index, and shrinkage limit values, and the constituent minerals were identified using X-ray diffraction. According to the results of the Atterberg’s limit tests, the soil samples taken from the city of Al-Faw fall into one of three categories: clayey silt low plasticity (ML), clay high plasticity (CH), or silty clay low plasticity (CL). The liquid limit in soil samples ranges between 34-55%, and the plasticity index values range between 12 and 28%. Three samples are of medium swelling potential, while the third location has high swelling potential and the second location has low swelling potential, and the X-ray diffraction data demonstrate that Montmorillonite is the main dominant clay mineral, accounting for an average of 31.88%, followed by Kaolinite mineral, which accounts for an average of 28.984%, Illite, which accounts for an average of 19.5702%, Chlorite, which accounts for an average of 12.1864%, and Palegorskite, which accounts for an average of 7.3688%.